Dramatic morphological changes in liposomes induced by peptide nanofibers reversibly polymerized and depolymerized by the photoisomerization of spiropyran - Liang, Yingbing; Ogawa, Shigesaburo; Inaba, Hiroshi; Matsuura, Kazunori (Frontiers in Molecular Biosciences, 2023)
Cytoskeletons such as microtubules and actin filaments are natural protein assemblies, which dynamically control cellular morphology by reversible polymerization/depolymerization. Recently, the control of polymerization/depolymerization of fibrous protein/peptide assemblies by external stimuli has attracted significant attention. However, as far as we know, the creation of an “artificial cytoskeleton” that reversibly controls the polymerization/depolymerization of peptide nanofiber in giant unilamellar vesicles (GUVs) has not been reported. Here, we developed peptide nanofiber self-assembled from spiropyran (SP)-modified beta-sheet-forming peptides, which can be reversibly polymerized/depolymerized by light. The reversible photoisomerization of the SP-modified peptide (FKFEC(SP)KFE) to the merocyanine-peptide (FKFEC(MC)KFE) by ultraviolet (UV) and visible light irradiation was confirmed by UV–visible spectroscopy. Confocal laser scanning microscopy with thioflavin T staining and transmission electron microscopy of the peptides showed that the SP-peptide formed -sheet nanofibers, whereas the photoisomerization to the merocyanine-peptide almost completely dissociated the nanofibers. The merocyanine peptide was encapsulated in spherical GUVs comprising of phospholipids as artificial cell models. Interestingly, the morphology of GUV encapsulating the merocyanine-peptide dramatically changed into worm-like vesicles by the photoisomerization to the SP-modified peptide, and then reversibly changed into spherical GUV by the photoisomerization to the MC-modified peptide. These dynamic morphological changes in GUVs by light can be applied as components of a molecular robot with artificially controlled cellular functions.